Influence of Tillage Systems and Selective Herbicides on Weed Management and Productivity of Direct-Seeded Rice (Oryza sativa) - ABBAS,A. (2019)
ABSTRACT: Weeds cause considerable damage to rice crop. To ascertain the influence of different weed management practices under different tillage systems, a field experiment was conducted during 2014-15. Experimental design was RCB with split-plot arrangement and with a net plot size of 6 x 2 m. Three tillage systems viz; zero tillage with glyphosate application and conventional tillage with and without stale seed bed, and seven weed management treatments viz; weedy check, manual weeding, oxadiargyl as pre-emergence, pyrazosulfuron as pre-emergence, pyrazosulfuron as post-emergence, fenoxaprop-ethyle + sodium fluoride as post-emergence and fenoxaprop-ethyle + sodium fluoride as post-emergence. Results revealed that all treatments including tillage systems and herbicides significantly (p<0.05) affected weed density and weed dry biomass. Minimum weed density (229.22, 159.22 and 127.77 m-2) and weed dry biomass (68.01, 49.29 and 41.08 g m-2) at 30, 45 and 60 DAS (days after sowing) were recorded for pyrazosulfuron (as pre-emergence), respectively, followed by fenoxaprop-ethyle + sodium fluoride (as post-emergence). Maximum 1000-kernel weight and kernel yield (19.15 g and 3.45 ton ha-1) were recorded for weed free treatments and it was 12 and 57% higher than weedy check. Maximum net benefit and benefit to cost ratio (USD$ 817 ha-1 and 1.76, respectively) were recorded for pyrazosulfuron applied at either pre- or post-emergence stage under zero tillage system. Conclusively, pyrazosulfuron (as pre-emergence) and fenoxaprop-ethyle + sodium fluoride (as post-emergence) gave the best weed control under conventional tillage with stale seed bed system, while pyrazosulfuron exhibited maximum benefit-cost ratio under zero tillage system.